2021
DOI: 10.1186/s13018-021-02530-2
|View full text |Cite
|
Sign up to set email alerts
|

T-614 attenuates knee osteoarthritis via regulating Wnt/β-catenin signaling pathway

Abstract: Background The aim of this study was to investigate the effect of Iguratimod (T-614) on rat knee osteoarthritis (KOA) and further to explore its underlying mechanism. Methods In this study, papain-induced KOA model was constructed. Hematoxylin and eosin (H&E) staining was conducted to observe the pathological changes of cartilage tissue and Mankin scoring principle was used for quantitative scoring. Transmission electron microscopy (TEM) was ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…In addition, AN could improve a series of biochemical indicators related to KOA in papain-induced rat KOA model. AN could decrease the levels of ROS, MDA, TNF-α, IL-6, IL-1β, IL-18, NO and PGE2, but increase the activity of SOD in the knee joint cartilage tissue to alleviate the papain-induced knee osteoarthritis in rats 32 , which are consistent with the results of previous study on the papain-induced knee osteoarthritis in rats 33 , and there were almost differences among the treatment groups in each experiment and the effects in AN-H group were most signi cant, indicating that the effects of AN were dose-dependent.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, AN could improve a series of biochemical indicators related to KOA in papain-induced rat KOA model. AN could decrease the levels of ROS, MDA, TNF-α, IL-6, IL-1β, IL-18, NO and PGE2, but increase the activity of SOD in the knee joint cartilage tissue to alleviate the papain-induced knee osteoarthritis in rats 32 , which are consistent with the results of previous study on the papain-induced knee osteoarthritis in rats 33 , and there were almost differences among the treatment groups in each experiment and the effects in AN-H group were most signi cant, indicating that the effects of AN were dose-dependent.…”
Section: Discussionsupporting
confidence: 91%
“…The intervention of CGG resulted in varying degrees of increased levels of COL2a1 and Aggrescan proteins in each group of rats compared to the model group, as well as decreased levels of MMP-3, MMP-13, and pro-inflammatory factors. Consistently, Cong et al 24 found that T-614 slowed KOA progression by reducing serum levels of IL-6 and TNF-α and inhibiting the secretion of serum MMP-13, thereby controlling the degradation of articular cartilage matrix. Briefly, CGG promote the synthesis of Col2 and Aggrescan, reduce the production MMPs, suppress the release of pro-inflammatory factors, thereby balancing the ECM and alleviating cartilage damage.…”
Section: Discussionmentioning
confidence: 68%
“… Lietman et al (2018) also confirmed that blocking of WNT/β-catenin signaling could improve the severity of OA in mice through mouse experiments. Cong et al (2021) showed that T-614 could inhibit joint inflammation by the WNT/β-catenin signaling pathway and inflammatory cytokines. However, the connections between these pathways and OA warrant further exploration and verification.…”
Section: Discussionmentioning
confidence: 99%